Participation in organised sports does not slow declines in physical activity during adolescence - O'Loughlin Jennifer; Gray-Donald Katherine; Bélanger Mathieu; Paradis Gilles; Hutcheon Jennifer; Maximova Katerina; Hanley James (BMC, 2009)
Abstract Background Among youth, participation in extracurricular physical activities at school and organised physical activities in the community is associated with higher physical activity levels. The objective was to determine if participation in organised physical activities during early adolescence protects against declines in physical activity levels during adolescence. Methods Every 3 months for 5 years, students initially in grade 7 (aged 12-13 years) completed a 7-day physical activity recall and provided data on the number and type of (extracurricular) physical activities organised at school and in the community in which they took part. To study rates of decline in physical activity, only adolescents who reported an average of ≥5 moderate-vigorous physical activity sessions per week in grade 7 (n = 1028) were retained for analyses. They were categorised as to whether or not they were involved in organised physical activities in grade 7. We used generalized estimating equation Poisson regression to compare the rate of decline in number of moderate-vigorous physical activity sessions per week during adolescence between initially physically active students who participated in organised physical activity in grade 7 and those who did not. Results In grade 7, about 87% of physically active adolescents reported taking part in at least one organised physical activity. Compared to active adolescents not involved in organised physical activities, baseline involvement in physical activity was 42% (95% CI 26-59%) higher among those involved in organised physical activity (mean number of moderate-vigorous physical activity sessions per week = 14.6 ± 13.1 vs 10.4 ± 9.0). Physical activity declined by 8% per year in both groups. Results were similar in analyses that examined the effect of school or community-based physical activities separately. Conclusion Although participation in organised physical activities during early adolescence is associated with more physical activity throughout secondary school, participation in such activities does not protect against declines in physical activity over time.